Improving Reading and Writing Skills of the Quran During the Month of Ramadan at PPWNI Klang - Agustina Kusmiyati; Nurjahri Nurjahri; Retika Nurnaningsi Umar; Harun Joko Prayitno (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
This research aims to improve the reading, writing, and memorization skills of the students of PPWNI Klang in the Quran, as well as motivate them to utilize the fasting month as an opportunity to delve into the meaning of the verses they read. This research involves four programs, namely: 1) Recycling Craft Making Practice, which teaches students to transform waste into useful items. 2) English Daily Class Program, which helps students enhance their English language proficiency. 3) Indonesian Cultural Literacy Program, introducing students to the richness of Indonesian culture. 4) Short Lecture Program, providing information on various Islamic topics. All programs utilize audiovisual media as effective and engaging learning tools. Before entering the fasting month, students have also received training in reading and writing the Quran, starting from daily prayers to Juz Amma. The methods used in this research include regular memorization every morning, memorization of daily prayers, memorization of prayer intentions for Salah, and an introduction to the fasting month. This research is expected to benefit students in terms of reading, writing, and understanding the Quran, as well as enhancing their understanding of Islamic teachings.